Vietnam : Technical Assistance Report-Report on Residential Property Price Statistics Capacity Development Mission. (IMF Staff Country Reports; Country Report ;, 2019)
A technical assistance (TA) mission was conducted during July 9-13, 2018 to assist the General Statistics Office of Vietnam (GSO) with the development of a residential property price index (RPPI). This was the first mission conducted to Vietnam under the auspices of the multi-annual STA Data for Decisions (D4D) trust fund. The main objective of TA provided to Vietnam under the D4D will be to assist the GSO to develop an RPPI. The GSO recently launched two initiatives to collect potential source data for the RPPI since taxation data are unreliable in respect of reported transaction prices, and the State Bank of Vietnam (SBV) does not collect loan level mortgage data.